Engagement of Nuclear Coactivator 7 by 3-Hydroxyanthranilic Acid Enhances Activation of Aryl Hydrocarbon Receptor in Immunoregulatory Dendritic Cells - Gargaro, Marco; Vacca, Carmine; Massari, Serena; Scalisi, Giulia; Manni, Giorgia; Mondanelli, Giada; Mazza, Emilia M. C.; Bicciato, Silvio; Pallotta, Maria T.; Orabona, Ciriana; Belladonna, Maria L.; Volpi, Claudia; et al. (Frontiers in Immunology, 2019)
Indoleamine 2,3-dioxygenase 1 (IDO1) catalyzes the first step in the kynurenine pathway of tryptophan (Trp) degradation that produces several biologically active Trp metabolites. L-kynurenine (Kyn), the first byproduct by IDO1, promotes immunoregulatory effects via activation of the Aryl hydrocarbon Receptor (AhR) in dendritic cells (DCs) and T lymphocytes. We here identified the nuclear coactivator 7 (NCOA7) as a molecular target of 3-hydroxyanthranilic acid (3-HAA), a Trp metabolite produced downstream of Kyn along the kynurenine pathway. In cells overexpressing NCOA7 and AhR, the presence of 3-HAA increased the association of the two molecules and enhanced Kyn-driven, AhR-dependent gene transcription. Physiologically, conventional (cDCs) but not plasmacytoid DCs or other immune cells expressed high levels of NCOA7. In cocultures of CD4+ T cells with cDCs, the co-addition of Kyn and 3-HAA significantly increased the induction of Foxp3+ regulatory T cells and the production of immunosuppressive transforming growth factor β in an NCOA7-dependent fashion. Thus the co-presence of NCOA7 and the Trp metabolite 3-HAA can selectively enhance the activation of ubiquitary AhR in cDCs and consequent immunoregulatory effects. Because NCOA7 is often overexpressed and/or mutated in tumor microenvironments, our current data may provide evidence for a new immune check-point mechanism based on Trp metabolism and AhR.